Factors Influencing the Use of E-Management from Manager's Perspective: An Applied Study in Saudi Communication Sector - Aseri, Abdulah M. (International Review of Management and Marketing, 2018)
Electronic Management (E-management) is considered as an important organizational mechanism that is critical for the effectiveness of decision making and control in organizations. The main purpose of this paper is to investigate the factors influencing the use of e-management in Saudi communication sector from manager's perspective. Data is collected through questionnaires from communication companies in Saudi Arabia. SmartPLS was used to analyze the data and to test the study hypotheses. Findings proof that perceived usefulness, ease of use and trust have a significant impact on using e-management. Keywords: E-management, electronic management, e-management factors, communication companies. JEL Classifications: M10; M15